Depression, sexual satisfaction, and other psychological issues in women with polycystic ovary syndrome. (3rd July 2018) - Stapinska-Syniec, Angelika; Grabowska, Klaudia; Szpotanska-Sikorska, Monika; Pietrzak, Bronislawa
Abstract: Polycystic ovary syndrome (PCOS) increases the risk of depression, poor quality of life, and low sexual satisfaction of women. The aim of the study was to evaluate the prevalence of these disorders and to assess the need for psychological consultation at the time of PCOS diagnosis. A case-control single-center study of 250 women who were diagnosed with PCOS voluntarily filled in an anonymous, interactive questionnaire. The inquiry form included 27 questions covering the woman's characteristics, satisfaction with their outer appearance and sexual life, as well as the Beck Depression Inventory (BDI). Based on the BDI, 52% (130/250) of studied women presented depressive symptoms. This group had significantly higher body mass index (29.5 ± 8.1 vs. 24.6 ± 5.8; p <.001) and a lower level of self-attractiveness than other studied women (3.3 ± 2.2 vs. 5.4 ± 2.3; p <.001). Forty two percent (106/250) of women viewed themselves as unattractive. A correlation between reduced sexual satisfaction and a sense of low attractiveness was noted ( r  = 0.465, p <.001). Sixty four percent (160/250) of women believed that psychological consultation should be offered to all PCOS women. Treatment of PCOS women should be multidisciplinary and include psychological counseling, especially in obese PCOS women with inadequate family support and dissatisfied with their sexual life.